Long-reads reveal that Rhododendron delavayi plastid genome contains extensive repeat sequences, and recombination exists among plastid genomes of photosynthetic Ericaceae - Li,Huie; Guo,Qiqiang; Li,Qian; Yang,Lan (PeerJ, 2020)
Background Rhododendron delavayi Franch. var. delavayi is a wild ornamental plant species in Guizhou Province, China. The lack of its plastid genome information seriously hinders the further application and conservation of the valuable resource. Methods The complete plastid genome of R. delavayi was assembled from long sequence reads. The genome was then characterized, and compared with those of other photosynthetic Ericaceae species. Results The plastid genome of R. delavayi has a typical quadripartite structure, and a length of 202,169 bp. It contains a large number of repeat sequences and shows preference for codon usage. The comparative analysis revealed the irregular recombination of gene sets, including rearrangement and inversion, in the large single copy region. The extreme expansion of the inverted repeat region shortened the small single copy, and expanded the full length of the genome. In addition, consistent with traditional taxonomy, R. delavayi with nine other species of the same family were clustered into Ericaceae based on the homologous protein-coding sequences of the plastid genomes. Thus, the long-read assembly of the plastid genome of R. delavayi would provide basic information for the further study of the evolution, genetic diversity, and conservation of R. delavayi and its relatives.
Keywords: Rhododendron; Ericaceae; Chloroplast genome; Repeat sequences; Gene recombination; Inverted repeat expansion; Phylogenetic relationship; Third-generation sequencing; De novo assembly; Chloroplast genome